2010
DOI: 10.2106/jbjs.j.00112
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Posterior Wall Fractures of the Acetabulum Treated Nonoperatively After Diagnostic Screening with Dynamic Stress Examination Under Anesthesia

Abstract: Hip joint stability determined with dynamic stress fluoroscopy with the patient under general anesthesia after a posterior wall acetabular fracture is predictive of hip joint congruity, an excellent radiographic outcome, and a good-to-excellent early clinical outcome after nonoperative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 17 publications
1
44
0
1
Order By: Relevance
“…The integrity of the posterior capsule may be responsible for this retained stability [22]. Others have suggested hip stability can only be assessed with intraoperative fluoroscopy and patients generally do well, with or without surgery, as long as the hip is stable [5,21]. However, biomechanical studies have found joint reaction forces increase as the size of the posterior wall fracture increases, leading to concern regarding longterm results [16].…”
Section: Limitationsmentioning
confidence: 99%
“…The integrity of the posterior capsule may be responsible for this retained stability [22]. Others have suggested hip stability can only be assessed with intraoperative fluoroscopy and patients generally do well, with or without surgery, as long as the hip is stable [5,21]. However, biomechanical studies have found joint reaction forces increase as the size of the posterior wall fracture increases, leading to concern regarding longterm results [16].…”
Section: Limitationsmentioning
confidence: 99%
“…However, none of the previous investigators has considered hip dislocation as part of the CT evaluation protocol. In addition, associated hip dislocation is reportedly not an important risk factor for residual instability of the hip [4].…”
Section: Discussionmentioning
confidence: 92%
“…Some investigators have described methods of predicting hip stability based on the size of the posterior wall fracture fragment as determined by 2-D CT [3,4,12,20]. Moed et al [13] recently compared hip stability status predictions using the method described by Calkins et al [3], the method described by Keith et al [5], and an alternative method [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations